PENDEKATAN TEMATIK DAN HERMENEUTIKA DALAM MENGKAJI PENDIDIKAN PERSPEKTIF AL-QUR’AN - Iqbal, Muhamad; Kadar M. Yusuf; Nur Indri Yani Harahap; Azly Prasetya Kurniawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education is one of the most important aspects of human life and receives significant attention in the Qur’an. Various verses of the Qur’an contain educational concepts related to the advancement of knowledge, the cultivation of moral character, the strengthening of faith, and the development of human potential. To comprehensively understand these educational concepts, an appropriate interpretive approach is necessary. This study aims to analyze the application of the thematic approach (tafsir maudhu’i) and hermeneutics in examining educational verses from the Qur’anic perspective, as well as to identify the strengths and limitations of these two approaches. This study employs a qualitative method using library research. Data were obtained from the Qur’an, tafsir texts, books, scientific journals, and various relevant literature, and were then analyzed using content analysis and descriptive analysis techniques. The results of the study indicate that the thematic approach is capable of compiling and integrating educational verses scattered across various surahs, thereby yielding a comprehensive understanding of the objectives, principles, and values of Islamic education. The hermeneutical approach helps to understand educational verses contextually by taking into account historical, social, and cultural aspects, as well as the needs of contemporary society. Both approaches have strengths in producing comprehensive and relevant interpretations, although they also have some limitations, such as the potential for subjectivity in interpretation and the possibility of verses being detached from their broader context. Therefore, the integration of thematic and hermeneutical approaches can serve as an effective alternative for understanding the concept of Qur’anic education in a deep, contextual, and practical manner for the development of Islamic education in the modern era.